2021
DOI: 10.1177/14034948211021724
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on mental health and health behaviors in Swedish adolescents

Abstract: Aims: There is an urgent need to explore the impact of the COVID-19 pandemic on adolescent mental health and health behaviours. To date, there are no such studies on Swedish adolescents. As COVID-19 emerged in the middle of our ongoing 2-year follow-up examination of the Study of Adolescence Resilience and Stress, we had the unique opportunity to use the corona outbreak as a ‘natural experiment’ to study the impact of COVID-19 on 15-year-old adolescents in Sweden. Methods: Adolescents (baseline age 13.6±0.4 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 22 publications
6
47
4
2
Order By: Relevance
“…No such information is available, however. The one study of adolescents in Sweden studying mental health during the pandemic using survey data finds no change in mental health among 16-year-olds (Chen et al 2021). This is in line with our finding of no change in mental health among lower-secondary students (aged 14-16).…”
Section: Discussionsupporting
confidence: 89%
“…No such information is available, however. The one study of adolescents in Sweden studying mental health during the pandemic using survey data finds no change in mental health among 16-year-olds (Chen et al 2021). This is in line with our finding of no change in mental health among lower-secondary students (aged 14-16).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, moderate-to-vigorous PA (MVPA) [ 69 ] and the number of steps significantly decreased [ 63 ]. The results of Chen et al [ 64 ] also showed a significant reduction solely in MVPA but did not reveal any changes in leisure-time exercise.…”
Section: Resultsmentioning
confidence: 93%
“…The remaining studies drew a heterogeneous conclusion. Chen et al [ 64 ] revealed a significant reduction in observed PA only for females while, in contrast, Elnaggar et al [ 80 ] and Sekulic et al [ 105 ] found this significant reduction only for males. The latter authors additionally detected a higher PA level at both measurement time points in boys.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations